Do Mothers Benefit from a Child-Focused Cognitive Behavioral Treatment (CBT) for Childhood Functional Abdominal Pain? A Randomized Controlled Pilot Trial - Claudia Calvano; Martina Groß; Petra Warschburger (MDPI AG, 2017)
While the efficacy of cognitive-behavioral treatment (CBT) approaches for childhood functional abdominal pain (FAP) is well-established for child outcomes, only a few studies have reported on parent-specific outcomes. This randomized controlled pilot trial analyzed effects of a group CBT on maternal variables (i.e., pain-related behavior, worries and self-efficacy, as well as general psychosocial strain). Methods: The sample constituted of 15 mothers in the intervention group (IG) and 14 mothers in the waitlist control group (WLC). Outcome measures were assessed pre-treatment, post-treatment and at three months follow-up. Results: Analyses revealed significant, large changes in maladaptive maternal reactions related to the child's abdominal pain in the IG compared to the WLC-i.e., reduced attention (d = 0.95), medical help-seeking (d = 0.92), worries (d = 1.03), as well as a significant increase in behaviors that encourage the child's self-management (d = 1.03). In addition, maternal self-efficacy in dealing with a child's pain significantly increased in the IG as well (d = 0.92). Treatment effects emerged post-treatment and could be maintained until three months follow-up. There were no effects on general self-efficacy and maternal quality of life. Conclusion: While these results are promising, and underline the efficacy of the CBT approach for both the child and mothers, further studies, including long-term follow-ups, are warranted.